Extension Program Design for Processing Coffee Leaves into Coffee Leaf Tea in Sampean Village, Sipirok District, South Tapanuli Regency - Doni Arfali Hasibuan; Iman Arman; Mahmudah (Darul Yasin Al Sys, 2026)
Coffee leaves obtained through selective picking before coffee plant pruning in Sampean Village, Sipirok District, South Tapanuli Regency, remain underutilized despite their potential to be processed into coffee leaf tea with added economic value. This study aimed to evaluate the suitability of an agricultural extension program design, assess coffee growers’ acceptance of the program, and determine changes in their knowledge and attitudes toward coffee leaf utilization. An evaluative research design with a quantitative descriptive approach was employed from April to May 2026. The study involved 66 coffee growers from seven farmer groups, with the sample size determined using the Slovin formula and participants selected through proportional stratified random sampling. Data were collected through observation, interviews, questionnaires, and documentation and analyzed using Likert scales, continuum analysis, and the normalized gain (N-Gain) test. The extension program comprised instructional materials on coffee leaf tea processing, lectures, practical demonstrations, discussions, printed folders, authentic tools and materials, and tutorial videos. The findings show that growers’ acceptance of the extension design reached 85.65%, indicating a very high level of acceptance. Their knowledge increased from 63.4% on the pre-test to 91.4% on the post-test, with an N-Gain score of 76.7%, categorized as high. Growers’ attitudes toward the innovation reached 88.45%, reflecting a very positive response. The study concludes that the extension program design was highly accepted and effective in improving growers’ knowledge and attitudes toward processing coffee leaves into coffee leaf tea. These findings provide practical implications for agricultural extension agencies and farmer groups seeking to promote the productive use of coffee by-products, strengthen innovation adoption, and create additional economic opportunities for coffee-growing communities.